The Role of Nurse in Caring for Children with Epilepsy - Siripoon, Prakaikaew (Journal of The Royal Thai Army Nurses, 2022)
Epilepsy is a common childhood brain disorder, which affects children physically, mentally, socially and intellectually, causing disabilities that affect the lives of children as well as their families and society. This health problem causes losses in both human resources and economy. If children with epilepsy do not receive the correct treatment and nursing care, their quality of life will be affected. Therefore, nurses who are important healthcare personnel should have the knowledge of the causes and the types of epilepsy, diagnosis, treatment and their effects on patients which are caused by epilepsy pathophysiology and complications from prolonged exposure to antiepileptic drugs. Nurses must have the ability to care for children with epilepsy. They must also perform the role of nurse in assessing patients, taking the history of epileptic seizures, performing physical examinations and analyzing laboratory results and special neurological examinations. This nursing roles must be performed in order to identify the nursing care problems, implement the nursing care process to develop a care plan to prevent complications from epileptic seizures and recurrent epileptic seizures, reduce anxiety for patients and their families, promote the potential of patients and their families in performing self-care at home as well as collaborating with local health services units and relevant people in the community to provide assistance in caring for children with epilepsy and their families.